The beginnings of medieval romance : fact and fiction, 1150-1220 - Green, D. H. (Dennis Howard), 1922-2008 (Cambridge studies in medieval literature ;, 2002)
Until the twelfth century writing in the western vernaculars dealt almost exclusively with religious, historical and factual themes, but the second half of the twelfth century saw the emergence of a new genre consciously conceived as fictional, the romance. Dennis Green explores how and why this shift occurred.